Axillary arch muscle - Sharma, T; Singla, RK; Agnihotri, G; Gupta, R (Kathmandu University Medical Journal, 2010)
Langer'arch is one of the rare muscular variation in the axillary region. In the present article, a case of 50 year old male cadaver with axillary arch in the right axillary region is being reported. It originated from anterior border of latissimus dorsi and merged with short head of biceps brachii. The embryological derivation, genetic basis and clinical implication of this muscular variant are also discussed. Key words: Axillary arch muscle; langer's arch; Panniculus carnosus DOI: 10.3126/kumj.v7i4.2770 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 432-434